Growth of Pinus radiata undergoing different thinning and pruning treatments in the Southeast of the province of Buenos Aires, Argentina - Ferrere, Paula; Lupi, Ana María; Boca, Teresa (BOSQUE, 2017)
Silvicultural treatments aim at increasing productivity in intervention stands. Bearing in mind the lack of prior information, the goals of this study are to assess the growth of Pinus radiata in the Southeast of the province of Buenos Aires, Argentina, and to promote the implementation of early intense pruning and thinning, assessing tree behavior at the individual and stand level. The trial was installed in a plantation of six years, with initial density of 1,111 plants ha-1, on a Hapludol ( <50 cm effective depth ) Treatments studied were: T1, control treatment, without intervention; T2, 50 % thinning, without pruning; T3, 75 % thinning, without pruning; T4, 50 % thinning, with pruning; and T5, 75 % thinning, with pruning. The trial was carried out in a six-year plantation, and measured yearly until the trees reached 13 years of age. Studied variables were: quadratic mean diameter, basal area and volume. Thinning had a significant and immediate impact on the production of wood at the stand level, whereas pruning did not led to significant growth losses, when applied in equivalent thinning intensities. Quadratic mean diameter increased differentially, with increases in the most intense thinning treatments. After 13 years, the most significant volume was found in T1 (189 m3 ha-1). When the growth of the 200 dominant trees was analyzed, treatments with 75 % thinning and with and without pruning differed statistically from the control. The intensity of 50 % thinning six years after plantation is the most recommended since it allows combining growth at the individual tree with a significant accumulation of volume remaining trees. Considering these soils do not compete with agricultural uses, these are interesting options to be considered as complementary productions.